TINGKAT SOSIALISASI DAN PEMAHAMAN MASYARAKAT TANI KELAPA SAWIT DALAM MENUNAIKAN ZAKAT MAL DI KABUPATEN TANJUNG JABUNG TIMUR - Fatimah, Siti; Devi, Erwina Kartika; Wandi, Wandi; Mun'amah, Anatun Nisa; Sarwono, Sarwono (Institut Agama Islam Ngawi, 2024)
Abstract, This article presents the findings of a field study aimed at understanding the perspectives of palm oil farmers regarding the implementation of zakat mal. Data were collected through observations, interviews, and documentation, with a descriptive analysis employed to portray the realities of zakat practices among these farmers.The findings indicate that palm oil farmers have not fully grasped the concept of zakat mal. Many perceive zakat and charity as similar, leading to contributions that often do not align with the established nishab. Their donations are more influenced by personal willingness and ability. Additionally, the timing of zakat contributions to the mosque is irregular; they give when they have the means and intent.This lack of understanding is primarily attributed to the insufficient outreach from relevant institutions, including Baznas, local government, and community leaders. Furthermore, the community struggles to locate payment sites for zakat mal due to the absence of zakat administrators in Tanjung Jabung Timur Regency. Keywords: Mal Zakat, oil palm farmers, Tanjung Jabung Timur.